Vocal Learning in Songbirds and Humans: A Retrospective in Honor of Peter Marler. (17th August 2015) - Soha, Jill A.; Peters, Susan; Foster, S.
Abstract Peter Marler made a number of significant contributions to the field of ethology, particularly in the area of animal communication. His research on birdsong learning gave rise to a thriving subfield. An important tenet of this growing subfield is that parallels between birdsong and human speech make songbirds valuable as models in comparative and translational research, particularly in the case of vocal learning and development. Decades ago, Marler pointed out several phenomena common to the processes of vocal development in songbirds and humans—including a dependence on early acoustic experience, sensitive periods, predispositions, auditory feedback, intrinsic reinforcement, and a progression through distinct developmental stages—and he advocated for the value of comparative study in this domain. We review Marler's original comparisons between birdsong and speech ontogeny and summarize subsequent progress in research into these and other parallels. We also revisit Marler's arguments in support of the comparative study of vocal development in the context of its widely recognized value today.